The Implementation of Project-Based Learning to Improve Students’ Participation and Interaction in Learning Arabic Language: A Focus on Writing Skills - Fitria Fitria; Munirul Abidin (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
One of learning models that has recently been widely applied is Project-based Learning (PJBL). PJBL is a learning model that provides space for educational actors who are directly involved in the classroom, namely teachers and students, to be jointly involved in a project to solve a problem. PJBL is widely applied to learning hard sciences such as Physics. So far, discussion of learning models that use PJBL in Arabic subjects is still relatively limited. This research aims to fill in the gaps in research and knowledge related to how to apply PJBL in learning Arabic in secondary education, especially in writing skills with the topics "School" (المدرسة) and "Hobbies" (هواية). This research was conducted at an Islamic Junior High School (SMP) located in the city of Malang, East Java in the 2021/2022 academic year using quantitative and qualitative research methods. The data in this study were obtained using written tests, interviews, and observations. The results showed that only about 12.6% of students scored above 70 for writing skills based on assessments on essay writing. Students also experience some difficulties in learning Arabic, both academically and psychologically. After implementing PJBL, students were known to have a positive response to PJBL and there was an increase in students' writing skills. However, this improvement can also be an aspect of improvement in future research because in this study, researchers looked at the results of students' writing that was worked on in groups, not on the results of individual work as during the initial assessment before PJBL was implemented.